2018
DOI: 10.1002/elps.201800079
|View full text |Cite
|
Sign up to set email alerts
|

Determination of protein charge variants with (imaged) capillary isoelectric focusing and capillary zone electrophoresis

Abstract: Biopharmaceuticals are increasingly present in pharmaceutical therapy. These highly complex molecules are still challenging for development and quality control. Charge heterogeneity is next to size heterogeneity, glycan analysis, or peptide mapping one main aspect of their thorough characterization. This review focuses on the charge-based analysis of biopharmaceuticals through CE. An overview is given about the three separation techniques cIEF, imaged cIEF and CZE for the analyses of charge variants, emphasizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 123 publications
0
28
0
Order By: Relevance
“…applied CE using coated capillary coupled via a sheathless interface to MS in parallel to other methods for analysis of a therapeutic peptide, aviptadil, and showed that CE‐MS is complementary to LC‐MS, especially with respect to detecting impurities. In total, these examples and additional published studies on CE‐MS in biopharmaceutical analysis indicate substantial potential in the context of manufacturing and quality control of biopharmaceuticals, as also outlined in detail in an excellent recent review .…”
Section: The Present: the Era Of Personalized Medicinementioning
confidence: 95%
“…applied CE using coated capillary coupled via a sheathless interface to MS in parallel to other methods for analysis of a therapeutic peptide, aviptadil, and showed that CE‐MS is complementary to LC‐MS, especially with respect to detecting impurities. In total, these examples and additional published studies on CE‐MS in biopharmaceutical analysis indicate substantial potential in the context of manufacturing and quality control of biopharmaceuticals, as also outlined in detail in an excellent recent review .…”
Section: The Present: the Era Of Personalized Medicinementioning
confidence: 95%
“…For this purpose, neutral capillaries using dynamic or permanent coating have been implemented. In cIEF, the most described coatings are LPA [54,57,59], hydroxypropyl methylcellulose (HPMC) [60,61] and PVA [62]. Concerning icIEF, a majority of reports in the literature described the use of a fluorocarbon capillary due to manufacturer's near monopoly (Proteinsimple) [55,[63][64][65].…”
Section: Glycan Analysismentioning
confidence: 99%
“…Authors concluded that their method used to separate native mAbs offers complementary results but extend five folds the analysis time and elicits a loss of sensitivity. The same year, Kahle et al realized a comparison of protein charge variants separated by CZE and cIEF to upgrade the quality control of batches [59]. Another approach on the development of innovative coating was performed by Xiao et al They reported an easy-to-use coating which gave a good separation of cetuximab (Erbitux®) and rituximab (Mabthera®) with respectively nine and five separated variants [88].…”
Section: Intact Analysismentioning
confidence: 99%
“…For this purpose, a CZE–CZE–MS approach was published recently . Due to the individual properties of different biopharmaceuticals, various modifications of the initial method from He and colleagues have been published . Goyon et al.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a CZE-CZE-MS approach was published recently [10]. Due to the individual properties of different biopharmaceuticals, various modifications of the initial method from He and colleagues [8] have been published [11][12][13]. Goyon et al demonstrated an alternative approach for the analysis of charge variants of mAbs using a BGE containing polyethylene oxide for dynamic coating and Bis-tris as a buffering agent.…”
Section: Introductionmentioning
confidence: 99%